An experimental investigation into the shear interaction between internal stirrups and external CFRP systems of RC beams - Teo, W. (International Association for Bridge and Structural Engineering (IABSE), 2015)
Extensive research effort has been conducted on the shear strengthening of reinforced concrete (RC) beams with externally bonded FRP systems. However there are still few aspects on their behaviour that are yet to be fully understood. One of them is the effect of shear interaction between internal shear reinforcement and the external FRP systems. Five strengthened RC beams were assembled and properly instrumented in this investigation to study the interaction between these two shear components. The results obtained are in agreement with many researches which indicated that addition of externally bonded FRP, as a matter of fact, preserves the integrity of internal transverse stirrups. With continuous FRP sheets and U-wrapped scheme, greater FRP contribution to the shear resistance can be expected.